2022
DOI: 10.2427/13124
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance patterns of Mycobacterium tuberculosis complex and risk factors associated with multidrug-resistant tuberculosis in the upper southern part of Thailand

Abstract: Background: this study aimed to assess the drug resistant pattern of Mycobacterium tuberculosis complex (MTBC) and the risk factors associated to multidrug-resistant tuberculosis cases (MDR-TB) in upper part of southern Thailand.  Methods: a total of 3238 TB cases was retrieved from a database of the office of prevention and control disease region 11. Only 1008 cases were confirmed by culture growth for Mycobacterium tuberculosis and drug-susceptibility testing (DST) during a period of 4 years (Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…However, our result was lower than the DR-TB proportion of 72.4% recorded in Bangalore and that of 76.4% indicated for Nigeria [23,26], but higher than those calculated in India (20.4%), Turkey (38.7%) and Northern Iran (8.2%) [22,24,25] and comparable to that of 69.4% found in Northern Kernataka [27]. The proportion of MR-TB in our study was lower than that reported for Turkey (37.8%) but higher than that (4.2%) for Bangalore [23,25]; however, the reported percentage of 9.1% for RR-TB in our study is comparable to those of 10.8% recorded in Northern Thailand and 10.2% determined in China [20,28]. According to the WHO, a rifampicin resistance of less than 3% for non-MDR-TB is a good quality performance indicator [29].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, our result was lower than the DR-TB proportion of 72.4% recorded in Bangalore and that of 76.4% indicated for Nigeria [23,26], but higher than those calculated in India (20.4%), Turkey (38.7%) and Northern Iran (8.2%) [22,24,25] and comparable to that of 69.4% found in Northern Kernataka [27]. The proportion of MR-TB in our study was lower than that reported for Turkey (37.8%) but higher than that (4.2%) for Bangalore [23,25]; however, the reported percentage of 9.1% for RR-TB in our study is comparable to those of 10.8% recorded in Northern Thailand and 10.2% determined in China [20,28]. According to the WHO, a rifampicin resistance of less than 3% for non-MDR-TB is a good quality performance indicator [29].…”
Section: Discussionsupporting
confidence: 82%
“…The low DR-TB odds in these zones might be largely attributed to poor access to and availability of diagnostic facilities for DR-TB, rather than to a low prevalence. This is in tandem with a report from South Thailand where people in the rural areas would most likely harbor DR-TB due to poor access to culture and DST for first-line drugs [20]. The situation in the Northeast is further compounded by the civil unrest caused by Boko Haram insurgents, resulting in socioeconomic problems, a major factor for the spread of DR-TB [21].…”
Section: Discussionmentioning
confidence: 65%